PENGARUH PENGGUNAAN MEDIA GAMBAR TERHADAP KEMAMPUAN MENULIS KARANGAN DESKRIPSI SISWA KELAS IX SMP PGRI 3 BANDAR LAMPUNG - Hastuti, Hastuti; Rachmasisca, Frieska Maryova (LPPM STKIP PGRI Bandar Lampung, 2021)
In the communication process there are 4 different but interrelated skills, the components of these language skills are listening, speaking, reading, and writing. Description writing skills need to be instilled in students. Composing in principle is telling about something that exists in the imagination. The story can be written orally or in writing. So to be able to write well, one must have the ability to write. The ability to write can be achieved through the process of learning and practicing. Based on the reality that there is an effect of using image media on the ability to write descriptive essays for class IX students at SMP PGRI 3 Bandar Lampung, there is data on the low ability to write descriptions for class IX students, it can be seen from students' essays that have not been able to create an impression of readers through their writings. Students' essays have not succeeded in bringing the reader as if they really saw the object in front of their eyes. The low writing skill is also caused by the difficulty of students expressing ideas or ideas into writing. The research method used in this research is experimental research. The results of the ANOVA calculation above show that Fcount = 18.78* which is greater than Ftable = 4.08 at a = 0.05 and Fcount at a = 0.01. The obtained value of Fcount = 31.23 which is greater than Ftable = 4.08 at a = 0.05 and Ftable = 7.31 at a = 0.01. This means Ho is rejected. Obtained 9.18 and Ttable = 6.038 for T(0.05) = 6.038 T (0.01) = 2.750 turns To > Ttable . Ho is rejected and H1 is accepted. There is an influence of low learning independence on students who have high learning independence between the application of image media and those who do not apply image media, namely by looking at the results of To = 1.16 < T table = 6.038; Ho is rejected.